Prognostic value of nucleated red blood cells in critically ill children (Swiss Medical Weekly, 2014)
QUESTION: Is there an association between the presence of nucleated red blood cells (NRBCs) in the peripheral blood and outcomes in critically ill children? METHODS: Prospective observational study conducted in 2008 (January to December) in a multidisciplinary paediatric intensive care unit (PICU) of a tertiary children’s hospital. We provide univariate analysis, stratified by age group (neonates and children >28 days of age), and multiple logistic regression, comparing clinically important outcomes (death, ventilation, renal replacement therapy, inotropic support) with haematological (NRBC, haemoglobin, platelets, leucocytes), illness severity (expected mortality [paediatric index of mortality, PIM2]), demographic (age, sex) and diagnostic parameters and length of stay. Haematological parameters correspond to the first 24 hours of PICU admission. RESULTS: Out of 670 patients, 195 (29.1%) were NRBC positive and 475 (70.9%) were NRBC negative. In the neonatal age group (n = 232), patients who died, were ventilated or received inotropic support had significantly more NRBCs than patients without these conditions (p = 0.032, 0.038 and 0.029, respectively). In the child age group (n = 438), only renal replacement therapy was significantly associated with NRBC (p